Fundamentals of Entrepreneurship (ENT 300) : Prang Badminton Hall / Nor Shazlyantie Wahap … [et al.] - Wahap, Nor Shazlyantie; Suhaili, Alllridha; Mohamad Azif Amin, Mohamad Syukri; Abdul Azis, Eza Nooraishah (2014)
Prang Badminton Hall is a business providing badminton court which offers two types of court; rubber court and cement court. The total numbers of courts provided are ten courts (five rubber courts and five cement courts). The location of this court is at Desa Ilmu, Kota Samarahan. Since there is only one competitor around the area, this badminton hall business will have more advantage due to latest services and new surrounding for the lovers of this indoor sport. This badminton court is not only place for customers to fill their leisure time, but also for those who like to enhance and hone their skills are most welcomed to our place.